Sistem Filtering Berbahan Daun Mangga Untuk Emisi Partikulat Matter2,5 - Purnama Sidebang; Alda Safitri; Rahdatia Magvira S Tarafannur; Ainurrahma Said; Nabila K Mafud; Gazali M Lahe (Jurnal Kesmas Jambi, 2022)
Abstract The annual growth of the vehicle industry sector has the potential to spur economic growth, but it can also harm the environment. The negative impact that can endanger human health is air pollution. Particulate Matter 2.5μm (PM2.5) is a very small air pollutant in size that can cause various diseases such as disorders of the respiratory tract if exposed to PM2.5 while exceeding the quality standard and continuously (55μg/m3 for daily quality standard and 15μg/m3 annual quality standard). This study aimed to see the effectiveness of the filtering system tool made from mango leaves and activated carbon to reduce PM2.5 emissions. This study was an pra-experimental research design with the one-group pre-post test design method. The population in this study is PM2.5 particulate emissions deriving from two motor vehicle emissions, emission source 1 (old two-wheeled motor vehicles) and emission source 2 (new two-wheeled motor vehicles). PM2.5 data were collected using the EVM-7 tool. The results showed a decrease in the concentration of PM2.5 before and after the mango leaf filter was installed on both emission sources. The average concentration of particulate matter decreases with the influence of different temperatures and humidity. It is recommended to continue this research to develop a filtering tool that can be used by the wider community to reduce air pollution, especially PM2.5. Keywords: PM2.5, Mango Leaf Filtering, Activated Carbon